If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3h + -2(4H + -5) = 10 + -5h Reorder the terms: 3h + -2(-5 + 4H) = 10 + -5h 3h + (-5 * -2 + 4H * -2) = 10 + -5h 3h + (10 + -8H) = 10 + -5h Reorder the terms: 10 + -8H + 3h = 10 + -5h Add '-10' to each side of the equation. 10 + -8H + -10 + 3h = 10 + -10 + -5h Reorder the terms: 10 + -10 + -8H + 3h = 10 + -10 + -5h Combine like terms: 10 + -10 = 0 0 + -8H + 3h = 10 + -10 + -5h -8H + 3h = 10 + -10 + -5h Combine like terms: 10 + -10 = 0 -8H + 3h = 0 + -5h -8H + 3h = -5h Solving -8H + 3h = -5h Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Add '-3h' to each side of the equation. -8H + 3h + -3h = -5h + -3h Combine like terms: 3h + -3h = 0 -8H + 0 = -5h + -3h -8H = -5h + -3h Combine like terms: -5h + -3h = -8h -8H = -8h Divide each side by '-8'. H = h Simplifying H = h
| -2y+4=8y-6 | | 8k-(6k-4)=10 | | x^6-3x^4+3x^2-1=250 | | x^6-3x^4+3x^2-1=1 | | k=(5a+3)(3a-2) | | (2x^2)-27x+55=0 | | 2(3x+y)=20 | | (0.75+0.25)-(0.25/0.5) | | 37-1/3 | | .12x-.5=.25(x-4) | | x-4/5=10 | | 5-x=7/2+4x | | x^2+3x+27=180 | | 4x-8=2(x+10) | | 2x-2+3x+15-6=0 | | 9+2(x-6)=21 | | 1/3x+2/3=-5/6-x/6 | | 5x+2=31x-50 | | 10y+3=9 | | 16000/400 | | 0.4p+1=0.7p-2 | | X=x+x+1/2x+1/4x+1 | | 7x+3x-(10x-2)=5+x | | 9/2y+8/y=1 | | x=3(8x-2)+7 | | 625=25*11+14*t | | 3x/5+7(x+1)=x/10-3 | | 5X+13=11X+6 | | 105x-23=85x+97 | | 105x-23= | | X^2/10+x+1.5=0 | | x/3+2=5/6x-7 |